2023
DOI: 10.1038/s41368-023-00243-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic analysis uncovers the origin and intratumoral heterogeneity of parotid pleomorphic adenoma

Xiuyun Xu,
Jiaxiang Xie,
Rongsong Ling
et al.

Abstract: Pleomorphic adenoma (PA) is the most common benign tumour in the salivary gland and has high morphological complexity. However, the origin and intratumoral heterogeneity of PA are largely unknown. Here, we constructed a comprehensive atlas of PA at single-cell resolution and showed that PA exhibited five tumour subpopulations, three recapitulating the epithelial states of the normal parotid gland, and two PA-specific epithelial cell (PASE) populations unique to tumours. Then, six subgroups of PASE cells were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Hence, there are genuine constraints associated with the targeting of AIM2. In the context of metabolic disorders, AIM2 has been identified as a possible target because AKT plays a crucial role in the regulation of glucose and lipid metabolism (H. Jin et al, 2023; L. Song et al, 2023; Xu et al, 2023). The modulation of glucose and lipid metabolism is crucial in the management of diverse metabolic disorders (H. Jin et al, 2023; L. Song et al, 2023).…”
Section: The Inflammasome‐independent Functions Of Aim2mentioning
confidence: 99%
“…Hence, there are genuine constraints associated with the targeting of AIM2. In the context of metabolic disorders, AIM2 has been identified as a possible target because AKT plays a crucial role in the regulation of glucose and lipid metabolism (H. Jin et al, 2023; L. Song et al, 2023; Xu et al, 2023). The modulation of glucose and lipid metabolism is crucial in the management of diverse metabolic disorders (H. Jin et al, 2023; L. Song et al, 2023).…”
Section: The Inflammasome‐independent Functions Of Aim2mentioning
confidence: 99%
“…As a result, fluorescence in-situ hybridization (FISH) can be used as a confirmatory test for PLAG1 (8q12) and HMGA2 (12q14.3) rearrangements to distinguish PA from other benign salivary gland tumors [6, 7]. In addition, more recent studies have shown copy number alterations on chromosome 12 which harbor important genes which may be genetic drivers of PA such as HMGA2, WIF1, MGP, and MUCL1 [20].…”
Section: Pleomorphic Adenomamentioning
confidence: 99%